Desarrollo de dispositivo para determinar las fuerzas en la unión socket-muñón en pacientes con amputación transfemoral (2015)
This article discusses the development of a device for determining forces in the union socket-stump determination of forces in the union socket-stump to real patients; the method used was by a data acquisition performed in 3 patients, each one with a transfemoral amputation condition level, Flexiforce sensors were used, which they were distributed in different áreas within the prosthesis. Through the Labview software and card data acquisition Arduino; It was performed for each patient a series of tests during the human gait cycle, which has the graphic result of strength and phase of the gait cycle, having in common that the phase with greater force recorded is the stance phase of monopodal made by the prosthesis.